Modified Miniskirt Bentall with an Annular Pericardial Patch for Bentall's Endocarditis - Akimasa Morisaki; Yosuke Takahashi; Kenta Nishiya; Toshihiko Shibata (The Thoracic & Cardiovascular Surgeon Reports)
Surgery for Bentall's endocarditis poses challenges because the infection spreads to the aortic valve annulus, leading to an annular abscess that necessitates reconstruction. We present a straightforward miniskirt Bentall procedure using an annular pericardial patch to treat Bentall's endocarditis with an annular abscess. After removing the former composite graft and debriding the aortic root and annulus, we created a miniskirt-composite graft using a mechanical or bioprosthetic valve, a straight or Valsalva graft, and an annular bovine pericardial patch with a valve prosthetic sizer. The miniskirt-composite graft, along with the underlying annular pericardial patch, was implanted using a double-layered suture technique.